Quality of life and radiation-induced late toxicity following intensity-modulated versus three-dimensional conformal radiotherapy for patients with spinal bone metastases: results of a randomized trial - Sprave, Tetyana; Verma, Vivek; Förster, Robert; Schlampp, Ingmar; Hees, Katharina; Bruckner, Thomas; Bostel, Tilman; El-Shafie, Rami; Nicolay, Nils; Debus, Jürgen; Rief, Harald (Anticancer research, 2018)
BACKGROUND/AIM: Quality of life (QOL) is becoming increasingly important to appraise the value of a particular oncologic intervention. This was a prespecified secondary analysis of a randomized trial (NCT02832830) of intensity-modulated radiotherapy (IMRT) versus conventional three-dimensional conformal radiotherapy (3DCRT) as part of palliative management of symptomatic spinal metastases. This study examined QOL, fatigue, emotional distress, and late toxicities between patients having received IMRT versus 3DCRT. - MATERIALS AND METHODS: Sixty patients were enrolled in this single-institutional randomized exploratory trial in which all patients received 30 Gy in 10 fractions. The EORTC QLQ-BM22, EORTC QLQ-FA13, and QSC-R10 questionnaires were utilized to evaluate QOL, fatigue, and emotional distress, respectively; endpoints were evaluated at baseline, and at 3, and 6 months. Late (6 months) toxicities were assessed according to the LENT-SOMA criteria. - RESULTS: Mean follow-up was 192 days (IQR=77-285). Although QOL was similar between groups, patients in the IMRT arm experienced lower physical (p=0.011) and emotional (p=0.017) fatigue at 6 months. Emotional distress was also lower in IMRT-treated patients after six months (p=0.039). Cohen's effect size confirmed the clinically significant improvement of these findings. Late toxicities occurred infrequently and were similar between arms. - CONCLUSION: This is the first randomized study evaluating QOL between IMRT and 3DCRT to palliate vertebral metastases. IMRT resulted in reduced physical and emotional fatigue as well as emotional distress. IMRT should be further studied for these patients given these outcomes.